Extreme Weather Events and Climate Change: Economic Impacts and Adaptation Policies - Susana Ferreira (Institute of Labor Economics (IZA), 2024)
This article reviews the literature on the economic impacts of disasters caused by extreme weather and climate events to draw lessons on how societies can better manage these risks. While evidence that richer, better governed societies suffer less and recover faster from climate extremes suggests adaptation, knowledge gaps remain, and little is known about the efficiency of specific adaptation actions. I review various "no or low" regrets adaptation options which are recommended when uncertainties over climate change impacts are high. I discuss how governments can play an important role in adaptation by directly providing public goods to manage disaster risks or by facilitating private agents' adaptation responses, but also highlight the political economy of policy and coordination failures.
Keywords: Q54; Q56; O13; O44; I30; 330; climate change policy; natural disasters; climate adaptation; risk management; climate extremes